Waste Management Practices in Selected Poultry Farms and its Effect on the Environment and Human Health in Makurdi, Nigeria - Abah, H.O.; Nwankwo, A.U.; Orgem, C.M. (International Journal of Environment, Agriculture and Biotechnology, 2019)
The poultry industry produces large amounts of waste that include solid waste and wastewater. These waste if not properly disposed can be risky to the environment and humans through the spread of diseases and pollution of soil and groundwater. The investigation to determine poultry waste management practices and its effect on the environment and human health was carried out in Makurdi. Benue State. The study was conducted from October to December 2017. A structured questionnaire was administered to 20 randomly selected poultry farmers and 20 neighbours in the study area by one on one interview and observation of the environment. Data collected from the questionnaires were analysed using descriptive statistics. The major poultry waste generated by the farms was faecal waste (50%) with about 50% of the respondents getting 25 bags or more of waste after clearance of poultry houses. There was no significant difference (P=0.056) between the flock size and the number of bags gotten from clearance of the litter. About (40%) of the farms sell their poultry waste immediately after clearing their farms while 30% applied theirs directly to nearby farm lands. The challenges in disposing of poultry waste were shortage of labour (45%) and lack of dumping sites (25%). The major complaint about poultry farms by neighbours living around the farms was bad odour (60%). It was observed that improper handling of poultry production waste from start to finish could lead to environmental and health hazards with 60% of the respondents reported being sick with signs of respiratory problems and 40% had digestive problems. Eighty-five (85%) percent of the farmers indicated that improper disposal of litter causes surface water contamination while all (100%) the farmers agreed that poultry waste causes air pollution. It was concluded that waste management by poultry farmers in the study area was inefficient. There is a need for further studies to assess the magnitude of the risk posed by poor poultry waste management practices to the environment, livestock and human health.